Innovative Interprofessional Education Model for Health Sciences Faculty: A Contextual Approach at UIN Alauddin Makassar - Yusuf, Saldi (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: This study aims to design and develop a contextualized Interprofessional Education (IPE) model for the Faculty of Health Sciences at UIN Alauddin Makassar, enabling students and faculty from Nursing, Midwifery, Pharmacy, and Public Health programs to improve collaborative competencies and prepare for effective interprofessional practice.Methodology: A mixed-method design combining quantitative surveys and qualitative focus group discussions was applied. Instruments included the Interdisciplinary Education Perception Scale (IEPS) and Readiness for Interprofessional Learning Scale (RIPLS). Data analysis employed descriptive statistics for quantitative data and thematic analysis for qualitative insights, integrated through a research and development (R&D) approach.Main Findings: Most students (92.3%) and faculty (90.9%) demonstrated positive perceptions of IPE, while readiness levels were high for students (92.3%) and all faculty (100%). Thematic analysis identified seven components for IPE implementation: expected competencies, learning methods, topics, timing, evaluation, facilities, and facilitator competencies, providing a comprehensive framework for effective interprofessional education.Novelty/Originality of this study: This study introduces a context-specific, faculty-wide IPE model integrating multiple health programs with interactive learning, ethical and communication topics, and practical simulations. It bridges global IPE frameworks with local educational culture, offering a feasible and adaptable approach that enhances interprofessional collaboration and prepares graduates for high-quality, patient-centered healthcare in Indonesia.